Regulated Expression of miR-155 is Required for iNKT Cell Development - Burocchi, Alessia; Pittoni, Paola; Tili, Esmerina; Rigoni, Alice; Costinean, Stefan; Croce, Carlo Maria; Colombo, Mario Paolo (Frontiers in Immunology, 2015)
Invariant Natural Killer T cells (iNKT cells) are CD1d-restricted, lipid antigen–reactive T lymphocytes with immunoregulatory functions. iNKT cell development in the thymus proceeds through subsequent stages, defined by the expression of CD44 and NK1.1, and is dictated by a unique gene expression program, including microRNAs. Here, we investigated whether miR-155, a microRNA involved in differentiation of most hematopoietic cells, played any role in iNKT cell development. To this end, we assessed the expression of miR-155 along iNKT cell maturation in the thymus, and studied the effects of miR-155 on iNKT cell development using Lck-miR-155 transgenic mice, that over express miR-155 in T cell lineage under the lymphocyte-specific protein tyrosine kinase (Lck) promoter. We show that miR-155 is expressed by newly selected immature wild type iNKT cells and turned off along iNKT cells differentiation. In transgenic mice, miR-155 over-expression resulted in a substantial block of iNKT cell maturation at Stage 2, in the thymus toward an overall reduction of peripheral iNKT cells, unlike mainstream T cells. Furthermore, the effects of miR-155 over-expression on iNKT cell differentiation were cell autonomous. Finally, we identified Ets1 and ITK transcripts as relevant targets of miR-155 in iNKT cell differentiation. Altogether, these results demonstrate that a tight control of miR-155 expression is required for the development of iNKT cells.